Seropositivity to caprine artritis encephalitis (CAE) virus and visna maedi (VM) in sheep and goats from semi-intensive and extensive farms in Lara state, Venezuela - Rojas, Raúl (2021)
The present work aimed to determine the presence of seropositivity to Caprine Lentivirosis Arthritis Encephalitis (CAE) and Maedi-Visna (MV) in sheep. In total, 260 goats and 30 sheep from extensive farms from 5 sectors, and 205 goats and 81 sheep from semi-intensive farms from 5 sectors were randomly selected, in both cases from Lara state, Venezuela. An epidemiological survey and clinical evaluation were carried out on each animal and blood samples were taken for serological analysis by the competitive ELISA technique. The general seropositivity was 6.25%. In the extensive flocks, three goats (1.46%) and three sheep (3.70%) were seropositive and in the semi-intensive flocks 30 goats were positive (11.54%) and no sheep. Most of the positive animals were 2- to 3-year-old goats, except for 1 month old kid. Of the seropositive animals, eight goats (22.2%) presented clinical signs and the rest were asymptomatic. The clinical signs were arthritis and chronic mastitis in goats and nervous symptoms in a kid. The circulation of the CAE/MV virus in goats and sheep is demonstrated, especially in farms of intensive technical goat farming in Venezuela and the presence of clinical signs compatible with the disease.